Improving the efficacy of musculoskeletal pain therapy: the role of B-group vitamins combination (descriptive review) - A. E. Karateev (Современная ревматология)
Controlling acute and chronic musculoskeletal pain (MSP) is a priority in the management of patients with musculoskeletal disorders. This includes widespread conditions such as non-specific back pain (NSBP), osteoarthritis (OA), and periarticular soft tissue disorders, affecting over 1 billion people worldwide. Modern therapy often fails to achieve satisfactory results in managing MSP: according to several studies, more than 50% of patients are dissatisfied with symptom control. This is due to the complex, multifactorial pathogenesis of MSP, involving persistent inflammation, inadequate tissue repair, nociceptive system dysfunction, biomechanical disturbances, and psycho-emotional factors.Therefore, the mainstay of pain management today is a multimodal approach that utilizes treatments and agents with different mechanisms of action to achieve a synergistic analgesic effect. One widely used strategy to enhance analgesic efficacy is the combination of analgesics with B-group vitamins (B1 – thiamine, B6 – pyridoxine, B12 – cyanocobalamin). B-vitamins exert a wide range of beneficial effects: they normalize neuronal energy metabolism, suppress peripheral and central sensitization, and possess anti-inflammatory, anabolic, and antioxidant properties. The combination of non-steroidal anti-inflammatory drugs with B-vitamins is commonly used in cases of acute NSBP and is included in current Russian treatment guidelines for this condition. The shared pathogenesis of MSP supports the rationale for the use of B-vitamins in managing pain associated with other musculoskeletal disorders, particularly OA.